Intrapersonal Communication Driving Childfree Decisions Among Unmarried Indonesian Women - Prayoga, Inggar; Junita Triwardhani, Ike (International Journal of Media and Communication Research, 2026)
The phenomenon of being childfree by choice is gaining traction in Indonesia, yet it remains a subject of significant social debate within the country's pronatalist culture. This study investigates the intrapersonal communication dynamics driving the proactive decision-making process of unmarried adult women who voluntarily choose not to have children. Adopting a qualitative research design with a phenomenological approach, data were collected through in-depth interviews and participant observations with five key informants and four supporting experts. The analysis is theoretically grounded in the integration of intrapersonal communication processes with the four phases of proactive decision-making: Intelligence, Design, Choice, and Implementation. The findings reveal that the decision to be childfree is fueled by a complex interplay of "because-motives," such as past exposure to dysfunctional family dynamics, and "in-order-to motives," including the pursuit of professional autonomy and emotional stability. The process initiates with the Intelligence phase, where individuals critically observe marital failures in their immediate environment. Subsequently, in the Design phase, they conceptualize alternative life trajectories that defy traditional gender roles. The Choice phase is characterized by a rational and value-based assessment of long-term financial and emotional risks versus the benefits of personal freedom. Finally, the Implementation phase manifests as a consistent integration of the childfree lifestyle into daily financial planning and social interactions. This study concludes that being childfree is not merely a rejection of parenthood but a profound exercise in self-identity and autonomy, requiring deep reflection to navigate societal expectations.